The Effect of Lavender Aromatherapy on Reducing the Scale of Menstrual Pain in Adolescent Girls at Al Anwar Boarding School, Cirebon Regency - Nurazizah, Nurazizah; Tonasih, Tonasih; Mutya Sari, Vianty; Nurjanah, Nunung (Jurnal Medisci, 2025)
Background: Based on data from the World Health Organization (WHO), the number of women with dysmenorrhea in the world is vast; on average, more than 50% of women in each country experience dysmenorrhea. Objective: This study aims to determine the effect of lavender aromatherapy on reducing the severity of menstrual pain in adolescent girls. Research Method: This study uses a quasi-experimental, two-group pretest-posttest design. The population in this study is adolescent girls aged 15-19 years at Al Anwar boarding school. by sampling using pretest and posttest data, and analyzed using the Paired t Test. So that 15 respondents will be researched. Results: The results of the paired sample t-test showed a ρ-value of 0.000 < 0.05, which means that there was an effect before and after the administration of lavender aromatherapy on the reduction of the scale of menstrual pain in adolescent girls at Al Anwar Boarding School, Cirebon Regency. Conclusion: This study found that the administration of lavender aromatherapy affected the reduction of menstrual pain in adolescent girls. Implementation. It is hoped that young women at Al Anwar Islamic Boarding School who experience menstrual pain can use lavender aromatherapy to reduce the level of dysmenorrhea pain.